A Smart Branding Strategy of Banyumas Traditional Dance’ Booklet at Dinas Komunikasi dan Informatika - Indah Puspita Mahdiyah (Program Studi Diploma Tiga Bahasa Inggris Fakultas Ilmu Budaya Unsoed, 2024)
This article is entitled “Creating an E-Booklet on Banyumas Traditional Dance as a Smart Branding Strategy of Dinas Komunikasi dan Informatika Banyumas”. The focus was on promoting traditional Banyumas dance by electronic booklet (e-booklet) as part of a smart branding strategy for the city, which has been recognized as a Smart City by SGAC (Smart Green ASEAN City) for its innovative waste management practices. The article emphasizes the creation of an English e-booklet aimed at enhancing global awareness of Banyumas traditional dances. Data was collected through observation, interviews with coordinator of Rumah Lengger and Maestro of Lengger dance, documentation included collecting photos and videos of traditional dances like ebeg and lengger. There are six stages of creating the e-booklet namely, illustration, text, typography, color, size, and layout. These stages are essential for creating the desired e-booklet design.